Comprehensive clinical commissioning and validation of the RayStation treatment planning system for proton therapy with active scanning and passive treatment techniques. (November 2017) - Bäumer, C.; Geismar, D.; Koska, B.; Kramer, P.H.; Lambert, J.; Lemke, M.; Plaude, S.; Pschichholz, L.; Qamhiyeh, S.; Schiemann, A.; Timmermann, B.; Vermeren, X.
Highlights: RayStation has been commissioned for treatment planning in proton therapy. By and large, the dose distribution in RayStation agrees with the dose in XiO. It has an accurate modelling of the lateral dose fall-off of passive fields. The computation of perturbed doses allows assessing the CTV coverage. Abstract: Purpose: To commission the treatment planning system (TPS) RayStation for proton therapy including beam models for spot scanning and for uniform scanning. Methods: Tests consist of procedures from ESTRO booklet number 7, the German DIN for constancy checks of TPSs, and extra tests checking the dose perturbation function. The dose distributions within patients were verified in silico by a comparison of 65 clinical treatment plans with the TPS XiO. Dose-volume parameters, dose differences, and three-dimensional gamma-indices serve as measures of similarity. The monthly constancy checks of Raystation have been automatized with a script. Results: The basic functionality of the software complies with ESTRO booklet number 7. For a few features minor enhancements are suggested. The dose distribution in RayStation agrees with the calculation in XiO. This is supported by a gamma-index (3 mm/3%) pass rate of >98.9% (median over 59 plans) for the volume within the 20% isodose line and a difference of <0.3% of V 95 of the PTV (median over 59 plans). If spot scanning is used together with a range shifter, the dose level calculated by RayStation can be off by a few percent. Conclusions: RayStation can be used for the creation of clinical proton treatment plans. Compared to XiO RayStation has an improved modelling of the lateral dose fall-off in passively delivered fields. For spot scanning fields with range shifter blocks an empirical adjustment of monitor units is required. The computation of perturbed doses also allows the evaluation of the robustness of a treatment plan.